Pengenalan Tarian Adat Dayak Hudoq Melalui Media Virtual Reality Untuk Pelestarian Budaya - Otovianus Oscar; Muhammad Ibnu Sa’ad; Jundro Daud Hasiholan (Bulletin of Information Technology (BIT), 2025)
Abstract- The preservation of the traditional Dayak Hudoq dance faces serious challenges due to globalization and the use of conventional learning media that are less appealing to the digital native generation. These challenges have resulted in a lack of understanding among the younger generation of the philosophical values of dance. There is a research gap in the use of Virtual Reality (VR) technology that focuses on the philosophical values of the dance and can be accessed independently (offline) using low-cost devices. This study aims to (1) develop an offline-based Virtual Reality educational application (VR-Box) using the Multimedia Development Life Cycle (MDLC) method, and (2) test the feasibility of this media as a means of cultural preservation. The MDLC method is applied through six systematic stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The testing process involved Alpha testing for functionality and Beta testing using a Likert scale questionnaire with 10 vocational high school students in Samarinda to measure ease of use and appeal. The results of the study show that the VR-Box application was successfully developed and functions well. The beta test results show a “Very Good” level of user acceptance with an overall average score of 88%. This application is considered very practical to use (96%) and capable of increasing interest in learning about culture (88%). It is concluded that the VR-Box application is feasible and effective to be implemented as a portable and low-cost medium for cultural preservation. However, user evaluation shows that visual quality (74%) is still an aspect that needs to be improved in further research. Keywords: MDLC, Visualization, Dayak, Cultural Preservation, VR